PEMBAHARUAN HUKUM PIDANA TERHADAP KRIMINALISASI GURU DALAM MENDISIPLINKAN SISWA MELALUI RESTORATIVE JUSTICE (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Acts of disciplinary action carried out by teachers, which in the past were consideredmediocre, are now considered to violate Human Rights (HAM). The difference in the twosides of the arrangement between Law Number 14 of 2005 concerning Teachers andLecturers and Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002concerning Child Protection raises differences in perceptions between teachers and parentsin terms of disciplining students to trigger there are legal problems due to differences in theview of legal protection for teacher actions in terms of disciplining students with protectionfor children. Based on these problems the author is interested to know first, how is the lawenforcement for teachers who are considered to conduct disciplinary actions against theirstudents based on several court decisions? Second, how is the renewal of the criminal lawagainst the criminalization of teacher cases in disciplining students through restorativejustice?This type of research is classified as normative legal research with a synchronizationtype of law. In normative law research, the data source is secondary data consisting ofprimary legal materials, secondary legal materials and tertiary legal materials. Normativelegal research data collection uses data collection techniques in the study of literature. Dataobtained through the study of literature will be analyzed qualitatively. In drawingconclusions the author uses the method of deductive thinking, namely the way of thinking thatdraws conclusions from a statement or general proposition into a statement that is specific.Based on the results of research and discussion it can be concluded that, First, how isthe law enforcement so far for teachers who carry out disciplinary actions against theirstudents based on several court decisions. In this case almost all law enforcement of teacherswho carry out disciplinary actions end up in prison. Law Enforcement Officials should payattention to the aspect of legal justice for a teacher who disciplines students in carrying outtheir profession in addition to requiring legal certainty and justice as well as legal settlementmust have a value of expediency. So that these events do not continue to happen again later.Secondly, in an effort to reform the criminal law, the settlement of the case can be donethrough non-penal efforts by applying the concept of restorative justice in order to maintainthe passion of teachers and educational institutions. mistakes made by teachers should beresolved beforehand through teacher professional organizations such as the IndonesianTeachers Honorary Council (DKGI), to assess whether these actions include violations of thecode of ethics or whether they are purely criminal acts which can later becomerecommendations to the police to process, of course, by applying the concept restorativejustice as a circular letter from the National Police Chief No .: SE / 8 / VIII / 2018 regardingthe Implementation of Restorative Justice (Restorative Justice), which must be supported by apolicy of renewing criminal law so that it can be properly and maximally applied.Keywords: Criminalization - Teacher - Restorative Justice- Criminal Law Reform